Evaluation of Corporate Sustainability Performance through the Integration of ESG and Balanced Scorecard in Manufacturing Companies in Indonesia - Samiun, Aspiati A.; Damau, Unika Oktaviani (West Science Accounting and Finance, 2024)
This study evaluates the corporate sustainability performance of manufacturing companies in Indonesia by integrating Environmental, Social, and Governance (ESG) criteria with the Balanced Scorecard (BSC). Using a quantitative analysis approach, data were collected from 200 manufacturing companies through a structured questionnaire employing a Likert scale ranging from 1 to 5. Structural Equation Modeling with Partial Least Squares (SEM-PLS 3) was utilized for data analysis. The findings indicate that all relationships between ESG criteria and BSC perspectives are positive and significant, suggesting that incorporating ESG factors into the BSC framework can effectively enhance corporate sustainability performance. This research contributes to the understanding of how ESG integration within traditional performance measurement tools can drive sustainable business practices in the manufacturing sector.